The Effect of Cutting Length and Coconut Water Concentration on the Success of Lemon Cuttings (Citrus Lemon L.) - Elviana, Elviana; Handayani, Rd. Selvy; Safrizal, Safrizal; Hafifah, Hafifah; Hendrival, Hendrival (Yayasan Pertanian Tropika Indonesia (YPTI), 2021)
Lemon (Citrus lemon L.) is one of the horticultural commodities used by Indonesian people in the form of juice or combined with cooking spices. The materials used for lemon cutting plants were topsoil, manure, coconut water, water, labeling paper, transparent plastic, and polybag size 12 x 17 cm. The tools used in this research were: hoe, machete, scissors, bucket, bamboo, paranet, raffia rope, meter, camera, watering can, measuring cup, scale, oven, and stationery. This research used Randomized Block Design (RBD) with a factorial pattern. The first factor was the length of the cuttings, and the second factor was the concentration of coconut water (0% (control), 25%, 50%, and 75%). It was repeated three times so that there were 36 experimental units.